Genetic Diversity and Pathogenic Potential of Attaching and Effacing Escherichia coli O26:H11 Strains Recovered from Bovine Feces in the United States - Ison, Sarah A.; Delannoy, Sabine; Bugarel, Marie; Nightingale, Kendra K.; Webb, Hattie E.; Renter, David G.; Nagaraja, Tiruvoor G.; Loneragan, Guy H.; Fach, Patrick (My University, 2015)
Escherichia coli O26 has been identified as the most common non-O157 Shiga toxin-producing E. coli (STEC) serogroup to cause human illnesses in the United States and has been implicated in outbreaks around the world. E. coli has high genomic plasticity, which facilitates the loss or acquisition of virulence genes. Attaching and effacing E. coli (AEEC) O26 strains have frequently been isolated from bovine feces, and there is a need to better characterize the relatedness of these strains to defined molecular pathotypes and to describe the extent of their genetic diversity. High-throughput real-time PCR was used to screen 178 E. coli O26 isolates from a single U.S. cattle feedlot, collected from May to July 2011, for the presence or absence of 25 O26 serogroup-specific and virulence-associated markers. The selected markers were capable of distinguishing these strains into molecularly defined groups (yielding 18 unique marker combinations). Analysis of the clustered regularly interspaced short palindromic repeat 1 (CRISPR1) and CRISPR2a loci further discriminated isolates into 24 CRISPR types. The combination of molecular markers and CRISPR typing provided 20.8% diversity. The recent CRISPR PCR target SP_O26-E, which was previously identified only in stx 2-positive O26:H11 human clinical strains, was identified in 96.4% (161/167 [95% confidence interval, 99.2 to 93.6%]) of the stx-negative AEEC O26:H11 bovine fecal strains. This supports that these stx-negative strains may have previously contained a prophage carrying stx or could acquire this prophage, thus possibly giving them the potential to become pathogenic to humans. These results show that investigation of specific genetic markers may further elucidate our understanding of the genetic diversity of AEEC O26 strains in bovine feces.